2008
DOI: 10.1111/j.1750-3841.2008.00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characteristics of Feruloyl Esterase from Aspergillus awamori G‐2 Strain

Abstract: For food industry production processes and other uses, a mold that produces high levels of feruloyl esterase was obtained from laboratory mold collections and other sources. It was Aspergillus awanmori G-2 that produces high levels of feruloyl esterase. The feruloyl esterase was purified using ion-exchange chromatography, size-exclusion chromatography, and HPLC chromatography. The enzyme was identified as a monomer protein using size-exclusion chromatography. Its optimum temperature and pH were, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 31 publications
(40 reference statements)
2
23
0
Order By: Relevance
“…There are a significant number of works concerning the purification and characterization of fungal FAEs produced by Aspergillus 9,22,32,40,56,65 , Sporotrichum 58,59 and Fusarium 57,60 species. The number of papers concerning the closer characterization of bacterial FAEs is much lower and some example microorganisms are Streptomyces 20,25,42 and Pseudomonas 24 Clostridium 15,35,41 .…”
Section: Release Of Phenolic Acids From Bsg By Fae Preparation From Lmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a significant number of works concerning the purification and characterization of fungal FAEs produced by Aspergillus 9,22,32,40,56,65 , Sporotrichum 58,59 and Fusarium 57,60 species. The number of papers concerning the closer characterization of bacterial FAEs is much lower and some example microorganisms are Streptomyces 20,25,42 and Pseudomonas 24 Clostridium 15,35,41 .…”
Section: Release Of Phenolic Acids From Bsg By Fae Preparation From Lmentioning
confidence: 99%
“…Phenolic acids present in barley and barley malt are mainly in the esterified form 36,37 and can be released into the gastrointestinal tract due to the action of bacterial ferulic acid esterases (FAE; EC 3.1.1.x) 12 . Different FAEs of fungal origin have been well characterized in the past 9,32,40,[56][57][58] . Bacterial FAEs produced by lactic acid bacteria (LAB) have been studied to a much lesser extent 16,48,62,63,66,71 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Kaminishi et al (1999) reported that Aspergillus has the ability to produce antioxidative substances. Lee et al (2007) and Bhanja et al (2009) refer the increase in the antioxidant activity of Asp.awamori to the increase of total phenolic and anthocyanin contents during the fermentation process, on the other hand Kanauchi et al (2008) showed that a natural material called feruloyl esterase could contribute in enhancing the antioxidative proprieties of Asp. awamori.…”
Section: Discussionmentioning
confidence: 99%
“…2b), with the enzyme remaining stable for at least 24 h at pH 5-7 and at least 1 h at 30°C to 60°C (data not shown). Optimum FAE activity at pH 6 was also reported for other Aspergillus FAEAs (Benoit et al 2008), whereas the higher enzyme stability in acidic conditions (retaining more than 80% activity at pH 3-7) corresponded to an A. awamori FAE (Kanauchi et al 2008). The optimum FAE activity at 50°C is within the temperature range of 35-55°C reported for other fungal FAEAs, including that of A. niger (Benoit et al 2008).…”
Section: Purification and Characterisation Of Recombinant Atfaeamentioning
confidence: 98%